Assessment of fish community structure along the Jakarta Bay–Pulau Seribu reef complex. (27th March 2018) - Polónia, A.R.M.; Cleary, D.F.R.; Duine, A.A.; Van Dijk, J.; De Voogd, N.J.
Abstract : Coastal ecosystems have been increasingly subjected to poor water quality. Remote sensing has been used to monitor water quality, but few studies have integrated remotely sensed data with compositional and/or abundance data of coral reef taxa. In the present study, fish biomass was assessed along the Jakarta Bay Thousand Island reef system and variation in the biomass of selected fish families related to substrate cover and remotely sensed data. Overall, fish biomass and the biomass of each of the families Acanthuridae, Apogonidae, Caesionidae, Chaetodontidae, Ephippidae, Pomacentridae, Labridae and the subfamily Scaridae were much higher mid- and offshore than inshore. Substrate cover and chlorophyll-a concentrations proved to be significant predictors of spatial variation in fish biomass, suggesting an important impact of reef degradation and eutrophication on reef fish abundance.